Worldwide research trends in Crohn's disease treatment over the past 2 decades: a bibliometric analysis - Likang Xu; Jinzhao Zou; Chao Sun; Gong Chen; Sujun Gao; Sujun Gao (Frontiers Media S.A., 2024)
BackgroundThe treatment of Crohn's disease (CD) has received widespread attention in clinical practice, but there is currently a lack of quantitative evaluation of the literature published in this field. This study aimed to describe the development trends and research hotspots of CD treatment through bibliometric analysis.MethodsPublications related to CD treatment published from 2004 to 2023 were searched in the WoSCC. Microsoft Office Excel 2021 was used for the analysis and visualization of the annual number of publications. CiteSpace was used to visualize the collaboration networks of authors, institutions, and countries, as well as to construct a reference timeline visualization map and identify keywords with the strongest citation bursts.ResultsThe bibliometric analysis included 25,608 publications between 2004 and 2023. The most productive year was 2021. The United States of America (n = 7,891) and the University of California System (n = 939) are the country and institution with the most published papers, respectively. Among the 97,564 authors, Peyrin-Biroulet, Laurent (n = 424) published the most articles. The core journals were Inflammatory Bowel Diseases, Journal of Crohns and Colitis, Alimentary Pharmacology and Therapeutics, etc. The timeline view showed that "#5 JAK Inhibitor" was the most recent topic. The keywords that burst and persist from 2020 to 2023 include "ustekinumab" and "vedolizumab".ConclusionAn increasing number of researchers are dedicating their efforts to exploring the treatment of CD, with the United States making the largest contribution to this field. Currently, the research hotspots predominantly involve drug therapy including ustekinumab, vedolizumab, and JAK inhibitors. Our study provides valuable information for scholars studying CD treatment.